Theories of Job Satisfaction and Job Performance - Ejiogu, Aloy M. (Lagos: Joja Educational Research and Publishers Limited, 1992)
In the book the author attempts to show how the extent to which individual needs are satisfied at work is closely linked to basic features of the model: the exercise of expertise, the demonstration of teacher commitment, the ability to obtain responsibility, the presence of teacher autonomy and the feeling of working in a collegial environment. Where the teacher has been able to enjoy these five areas of activity their job satisfaction, it has been able to enjoy these five areas of activity their job satisfaction, it has been assumed, has been automatic concomitant of the professionalism of the teacher.
Includes Bibliographic references
rpm 21/02/2018
Loans
Keywords: Job Satisfaction; Job Performance